Immunotherapy prospects in the treatment of lung cancer and mesothelioma - Aerts, Joachim G. (Transl Lung Cancer Res, 2014)
A very recent finding is the role of immune activation in cancer. The assumption that stimulating the patient’s immune system to attack tumors is a valuable treatment option in malignant diseases has gained more acceptance. However the high immunosuppressive effects caused by the tumor limits this beneficial effect. There is a delicate balance between immunoactivation and immunosuppression in a patient. Especially in non small cell lung cancer (NSCLC), the role of immunosuppressive cells hampering immune activation is high. But also in small cell lung cancer (SCLC) and mesothelioma immunosuppressive activity is high. This is suggested to be related to the type of tumor, advanced stage of the disease, and the tumor load. In this review, we provide an overview of the progress and challenges in the immunotherapeutic approaches in lung cancer. We conclude with the concept that immunotherapy in thoracic malignancies must be tailored made to the balance of the immune system.